2021
DOI: 10.1101/2021.06.07.21258225
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Health-related quality of life of female sex workers living with HIV in South Africa: a cross-sectional study

Abstract: Background: Health-related quality of life (HRQoL) is an important HIV outcome beyond viral suppression. However, there are limited data characterizing HRQoL of key populations including female sex workers (FSW) living with HIV. Methods: We used baseline data (2018-2020) of FSW who were diagnosed with HIV and enrolled into a randomized trial in Durban, South Africa. HRQoL information was collected by a generic preference-based tool with five domains (EQ-5D), and summarized into a single score (range 0-1) whi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…The model using overall QoL showed that enacted sex work stigma, internalized sex work stigma and enacted HIV stigma were associated with a decrease in prevalence of high overall QoL. Another analysis using the same study population similarly linked internalized stigma with overall QoL using the EuroQoL five dimension, three-level questionnaire (EQ-5D-3L) [63]. This previous analysis also reported that increased internalized and experienced stigma were associated with a lower EuroQoL visual analogue scale (EQ-VAS).…”
Section: Discussionmentioning
confidence: 95%
“…The model using overall QoL showed that enacted sex work stigma, internalized sex work stigma and enacted HIV stigma were associated with a decrease in prevalence of high overall QoL. Another analysis using the same study population similarly linked internalized stigma with overall QoL using the EuroQoL five dimension, three-level questionnaire (EQ-5D-3L) [63]. This previous analysis also reported that increased internalized and experienced stigma were associated with a lower EuroQoL visual analogue scale (EQ-VAS).…”
Section: Discussionmentioning
confidence: 95%